Pelatihan dan Sosialisasi Aplikasi Pengajuan Tugas Akhir (Skripsi) Berbasis Online - Suhaidi, Mustazzihim; Satria, Devit; Harfida, Elisa; Mahmud, Soni Fajar; Wati, Lidya (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
Final Project is a term used in Indonesia to illustrate a scientific paper in the form of exposure to written research results, discussing a problem in a particular field of science by using applicable rules. STIA Lancang Kuning is still not effective and efficient in terms of campus services for final year students, especially when submitting the final project title because it still uses manual methods. The file study program is recapsed one by one into Microsoft Excel, so there is a high risk of data input errors due to human error, not to mention the possibility of duplicate titles that could have occurred, where titles that have been submitted can be submitted again by other students. The process needs to be supported by implementing technology, namely by using the web as an implementing medium. The author uses the PHP programming language and MYSQL database which aims to build an information system for the final project title submission which is expected to support and facilitate the process of submitting the final project title and easily obtain information about campus services, especially when submitting a final project at STIA Lancang Kuning.